Transformations of organic compounds in the open intercepting sewer = Przemiany związków organicznych w otwartym kanale ściekowym - Myszograj, Sylwia; Sadecka, Zofia; Suchowska-Kisielewicz, Monika; Płuciennik-Koropczuk, Ewelina; Qteishat, Omar (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The paper presents results of studies concerning the designation of COD fraction in the raw wastewater. The test object was open intercepting sewer of Zielona Góra. Methodology for determining the COD fraction was based on the guidelines ATV- A 131.
Keywords: proces biochemiczny; frakcja COD; kanał ściekowy otwaty; kaskadowy przepływ ścieków; biochemical process; dissolved oxygen; COD fraction; open intercepting sewer; cascade